DEVELOPMENT OF COMIC-BASED TEACHING MATERIALS TO IMPROVE STUDENT LEARNING OUTCOMES ON WATER CYCLE MATERIALS IN CLASS VC SDN MAULAFA KUPANG CITY - Bernadino Ceunfin; Yulsy Marselina Nitte; Heryon Bernard Mbuik (Universitas Citra Bangsa, 2025)
This research aims to develop comic-based teaching materials that are feasible, attractive, practical, and effective to improve student learning outcomes on water cycle materials in the VC class of SDN Maulafa Kupang City. The research method uses a Research and Development (R&D) approach with the ADDIE model which includes needs analysis, design, development through expert validation, trial implementation, and evaluation. The research subjects consisted of 29 students, with instruments in the form of expert validation questionnaires, teacher and student response questionnaires, and learning outcome tests. The results of the study showed that the comic teaching materials received very decent assessments from material experts (98%), linguists (90%), media experts (97%), teacher responses (97%), and student responses (93%). Student learning outcomes also increased significantly, with an average pretest score of 79% rising to 88% on the posttest (very good category). The gain test value of 0.84 (>0.7) indicates an increase in the high category. Data analysis using the t-test with the help of SPSS version 23 shows that the data is normally distributed so that it can be analyzed parametrically. The test results showed a Sig. (2-tailed) value < 0.05, which means Ho was rejected and Ha was accepted. Thus, the use of comic-based teaching materials has a significant effect on improving student learning outcomes. This study concludes that comic-based teaching materials are effectively used and can be an innovative alternative in learning science science in elementary schools, especially in water cycle materials.